Obstetrical Management of Severe Hypertriglyceridemia in Pregnancy: A Case Report - Nigel Madden; Nevin Kamal; Jared Friedman; Priya Freaney; Susan E. Gerber; Emily D. Szmuilowicz (American Journal of Perinatology Reports, 2024)
Background Pregnant people with baseline hypertriglyceridemia are at increased risk of severe hypertriglyceridemia and the associated complications, yet there are no formal recommendations to guide management of these patients during pregnancy.